2021
DOI: 10.3390/ijerph182212182
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Influencing Factors on Spatial Spread of COVID-19 Based on Geographical Perspective

Abstract: The COVID-19 outbreak is a manifestation of the contradiction between man and land. Geography plays an important role in epidemic prevention and control with its cross-sectional characteristics and spatial perspective. Based on a systematic review of previous studies, this paper summarizes the research progress on factors influencing the spatial spread of COVID-19 from the research content and method and proposes the main development direction of geography in epidemic prevention and control research in the fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Assessing the spatial distribution of the COVID-19 pandemic at different scales Geographical analysis has been widely applied to study the spatial distribution and the spread of the COVID-19 epidemic at different scales such as the global scale (16-18), regional scale (19,20) and the country or state scale (21,22). A typical study at the global scale was carried out when a sample of 186 countries divided into four main regions, notably: Asia-Pacific and the Middle East, Europe, Africa and America was used successfully to study the effectiveness and consequences of Covid-19 measures (16).…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the spatial distribution of the COVID-19 pandemic at different scales Geographical analysis has been widely applied to study the spatial distribution and the spread of the COVID-19 epidemic at different scales such as the global scale (16-18), regional scale (19,20) and the country or state scale (21,22). A typical study at the global scale was carried out when a sample of 186 countries divided into four main regions, notably: Asia-Pacific and the Middle East, Europe, Africa and America was used successfully to study the effectiveness and consequences of Covid-19 measures (16).…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study reported that changes in BMI among adults were not associated with the location of residence [44]. The significant increase in the prevalence of hypertension seen only in urban areas might be associated with the following: (1) Urban areas have dense populations [45]. Thus, the impact of COVID-19 on hypertension might be higher in urban areas compared to rural areas; (2) environmental factors, including sleep patterns and screen time, might contribute to this difference [37], and (3) larger sample sizes in urban areas compared to rural areas might have contributed to this statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Ces résultats sont similaires avec ceux obtenus par Naumov et al (2021). Ils sont aussi conformes à la synthèse des résultats empirique faite par Xie et al (2021) sur l ' importance de l ' environnement naturel et du niveau de développement économique dans la propagation de la pandémie. L ' activité économique s ' accompagnant souvent de fortes concentrations dans les villes et métropole est propice à la propagation du nouveau coronavirus.…”
Section: Sur Les Données éConomiquesunclassified